GREEN IMPACT: EXPLORING THE MOTIVATIONS BEHIND SUSTAINABLE FASHION SHOPPING AND CONSUMPTION TOWARD GREEN APPAREL IN INDONESIA - Pratiwi Diyan Ayu Anggraini; Erlita Ridanasti (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research adopts shopping motivation theory (utilitarian and hedonic) as a framework. The aim of this research is to investigate the impact of shopping motivation on consumers’ purchase intentions in the context of environmentally friendly clothing. Data were collected through a questionnaire survey of 185 respondents in Indonesia and analyzed using the SmartPLS v.4.0.0 tool with the SEM (Structural Equation Modeling) analysis. This research shows that utilitarian and hedonic motivations have a positive and significant effect on green purchase intention. Availability of information and special offers also have a positive and significant effect on utilitarian motivation, trends, adventure, and authority, and status. These findings will help managers and practitioners to promote sustainable consumption through environmentally friendly clothing. This can encourage cleaner production and sustainable consumption practices that benefit both the planet and people.